Monetary Transmission Mechanisms in Belarus - Maino, Rodolfo (IMF Working Papers; Working Paper ;, 2006)
We explore monetary policy transmission by estimating VAR impulse response functions to illustrate the Belarusian economy's response to unexpected changes in policy and exogenous variables. We find a significant exchange rate pass-through to prices, and interest rate policy following, rather than leading, financial market developments. Our estimated monetary policy reaction function shows the central bank striking a balance between real exchange rate stability and containing inflation. We discuss dollarization, administrative interventions, and other features complicating monetary policy transmission, review specific constraints and vulnerabilities, and conclude with observations on possible measures that could raise the effectiveness of monetary policy in Belarus.